5-2(x+1)=27

Simple and best practice solution for 5-2(x+1)=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-2(x+1)=27 equation:


Simplifying
5 + -2(x + 1) = 27

Reorder the terms:
5 + -2(1 + x) = 27
5 + (1 * -2 + x * -2) = 27
5 + (-2 + -2x) = 27

Combine like terms: 5 + -2 = 3
3 + -2x = 27

Solving
3 + -2x = 27

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -2x = 27 + -3

Combine like terms: 3 + -3 = 0
0 + -2x = 27 + -3
-2x = 27 + -3

Combine like terms: 27 + -3 = 24
-2x = 24

Divide each side by '-2'.
x = -12

Simplifying
x = -12

See similar equations:

| -3.1=450/x | | 11(z+1)-4(z-3)=4(z-1)+2(z-1) | | 6(2x+9)=-8+2(x-9) | | -5+10(i+5)=-6 | | 3y+4=8y-5 | | 7p-9=4p | | 3(3y-8)-2(y+4)= | | 4y-20x=28 | | 1.3+0.3+x=0 | | 2(x+3)=5(x-1)-1 | | 2(1+4x)=58 | | (60x^2y)-(70x^4zw)=0 | | 5(-2n-3)+8n=-11 | | 3(1+5x)=153 | | 0.5c-0.07+0.1c=0.23 | | 9(b-x)=7b+ax | | 6(4x+5)=126 | | 9x+5x+4+8=3x+4+10x | | x-3+8=9 | | 4(1+7m)=4 | | 7x-22=132 | | 3y=-4+x | | 6(5+3x)=246 | | 3x+20-5x=5+x | | Y=60-24+2X | | -2(2k-5)-2(k+7)-11k= | | 6(5+3x)=228 | | x-9+6=8 | | 150+16x=100+8x | | 7(6x+9)=357 | | -3u-w=u-5w | | 7(6x+4)=238 |

Equations solver categories